The contribution of voluntary sustainability systems to women’s participation and leadership in decision-making: A strategic evidence review - Morgan, Miranda; Zaremba, Haley (2023)
As more Voluntary Sustainability Standards/Systems (VSS) increase their efforts to address gender inequality in agri-food value chains, the timing is ripe to reflect on progress to inform future strategies and research. This paper revisits the body of evidence on VSS and gender equality through the lens of SDG5.5 specifically, to identify if and especially how VSS may support women’s full and effective participation and equal opportunities for leadership in decision-making in rural communities. The objectives of this strategic evidence review were two-fold: first, to review what the existing research on VSS and gender equality reveals on the contributions made specifically to women’s participation and leadership in decision-making; and secondly, to identify knowledge gaps to inform the direction of future research on this topic.